2021
DOI: 10.1186/s12880-021-00615-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visceral artery involvement in patients with peripheral artery disease found on run-off MRA

Abstract: Background In patients with peripheral artery disease (PAD), run-off MR-angiography (MRA) is a commonly performed diagnostic test to obtain high-resolution images for evaluation of the arterial system from the aorta through the distal run-off vessels. The aim of this study was to investigate the prevalence of visceral artery involvement (VAI) in patients with PAD and leg symptoms examined with run-off MRA. Methods We retrospectively analyzed 145 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another study revealed that visceral artery stenosis may coexist in almost 50% of patients with peripheral artery disease. 6 Both symptomatic subclavian artery stenosis and stenosis above 50% of the carotid artery associated with symptoms have indication for interventional treatment, 1 which also represented the first step in the management of our patient. Of particular importance is that peripheral arterial occlusive disease associated with coronary or cerebrovascular disease significantly increases the risk of mortality caused by cardiovascular or cerebrovascular events.…”
Section: Discussionmentioning
confidence: 90%
“…Another study revealed that visceral artery stenosis may coexist in almost 50% of patients with peripheral artery disease. 6 Both symptomatic subclavian artery stenosis and stenosis above 50% of the carotid artery associated with symptoms have indication for interventional treatment, 1 which also represented the first step in the management of our patient. Of particular importance is that peripheral arterial occlusive disease associated with coronary or cerebrovascular disease significantly increases the risk of mortality caused by cardiovascular or cerebrovascular events.…”
Section: Discussionmentioning
confidence: 90%
“…Several published studies investigated calcifications of the abdominal aorta and its branches with inconclusive results [18][19][20], and the clear effect of the visceral and ectopic fat on abdominopelvic arteries remained under investigated. We think that the non-contrast multislice CT (MSCT) scan of the abdomen and pelvis can reveal the associations of fat tissue accumulation and the atherosclerotic calcifications of abdominopelvic arteries.…”
Section: Introductionmentioning
confidence: 99%
“…PAD is associated with other atherosclerotic syndromes, including chronic mesenteric ischemia and stenosis of other arteries that supply visceral organs [13]. We hypothesize that in patients with PAD who are predisposed to atherosclerosis, endothelial dysfunction of vessels supplying the biliary system can potentially impair post-procedural healing, thereby predisposing one to complications such as bleeding, infection, and perforation after trauma caused by ERCP.…”
Section: Introductionmentioning
confidence: 99%